Development of TIO₂ nanotube and SNO₂ nanofiber supported gold nanoparticle based non-enzymatic H₂O₂ sensors and its practical applications - Md. Ashraful, Kader (2023)
Electrochemical sensors, a state-of-the-art technological tool at the time, provide realtime monitoring capabilities, allowing convenient and rapid analysis of specific compounds in various domains. However, the intrinsic shortcomings such as low signal strength, denaturation, low stability and high maintenance cost plague the widespread use of conventional redox protein and enzyme-based H2O2 sensors. To address these limitations, porous metal oxide, titanium dioxide nanotube (TiO2 NTs) and Tin(IV) oxide nanofiber (SnO2 NFs) supported gold nanoparticle (Au NPs) catalyst-based enzyme free electrochemical sensor was developed to detect H2O2. The work commenced with the synthesis of 4-5 nm size Au NPs, anatase TiO2 NTs and multiporous SnO2 NFs via citrate reduction, electrochemical anodization and electrospinning method, respectively. The first composite electrode, Au NPs/TiO2 NTs was prepared by distributing Au NPs within the pores of anatase TiO2 NTs via drop casting, confirmed via surface characterization using Field Emission Scanning Electron Microscope (FESEM) and X-ray Powder Diffraction (XRD). Another GCE/Au NPs/SnO2 NFs composite electrode was fabricated by depositing Au NPs along with SnO2 NFs support onto a glassy carbon electrode (GCE). Characterization using Transmission Electron Microscope (TEM) and X-ray Diffraction (XRD) showcasing the coexistence of both Au NPs and SnO2 NFs within the composite. Both porous TiO2 NTs and SnO2 NFs have unique properties that trap Au NPs in their porous structure, preventing aggregation and accelerating electron transfer, leading to significantly higher current response during H2O2 sensing. The electrochemical investigation of Au NPs/TiO2 NTs and GCE/Au NPs/SnO2 revealed that Au NPs on the electrode exhibited distinct peaks and were the sole material showing catalytic response with the help of TiO2 NTs and SnO2 NFs support. During multiple step chronoamperometry at a potential of -0.35 V, the Au NPs/TiO2 NTs composite electrode demonstrated a speedy response within 1.55 s towards H2O2 where linearity, sensitivity, and detection limits of 1 μM to 5.413 mM, 519.38 μA/mM, and 104.4 nm, respectively. On the other hand, GCE/Au NPs/SnO2 displayed quite faster linear response towards the addition of 49.98 μM to 3.937 mM of H2O2 where sensitivity and LOD were calculated to be 14.157 μA/mM and 6.67 μM, respectively. In addition to this, both sensors exhibited strong immunity towards interfering substances, good performance accuracy and long-term response stability. In the last part, the Au NPs/TiO2 NTs composite sensor was examined with tap water, milk and bacteria and the GCE/Au NPs/SnO2 sensor was tested with tap water, apple juice and bacteria where they both exhibited good recoveries of H2O2 with acceptable relative standard deviations. Overall, Au NPs/TiO2 NTs and Au NPs/SnO2 composite based sensors are very promising in electrochemical sensing technology. With their low detection limit, long-term stability and higher real sample recovery, these composites breathe new life into the possibility of detecting H2O2 in various environments, like a mystical potion that overcomes the problems of traditional biosensors.